2021
DOI: 10.21203/rs.3.rs-221121/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-racial Consistency of Sexual Dimorphism in Facial Forms: Comparisons Between Turkish and Japanese Populations

Abstract: Facial features may reflect an individual’s probability of survival because of natural selection—for example, through reproduction and feeding abilities. However, questions remain about which facial characteristics contribute to facial masculinity and/or femininity across races. Given that sexual dimorphism stems from the common natural selection process, it is hypothesized that there is cross-racial consistency in sexual dimorphism of facial forms. Examining the extent to which sex differences in facial soft … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Maasai being one of such examples. Some findings suggest that prenatal testosterone exposure may affect the sexually dimorphic facial morphology [ 17 ], and androgens in males could contribute to facial sexual dimorphism both before and after puberty [ 34 ]. The data from two traditional East African populations, one of which is seminomadic pastoralists similar to Maasai in their ecology and cultural patterns (the Datoga), pointed to the potential role of androgen receptor gene polymorphism in male aggression and reproduction (number of offspring born) [ 148 , 149 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maasai being one of such examples. Some findings suggest that prenatal testosterone exposure may affect the sexually dimorphic facial morphology [ 17 ], and androgens in males could contribute to facial sexual dimorphism both before and after puberty [ 34 ]. The data from two traditional East African populations, one of which is seminomadic pastoralists similar to Maasai in their ecology and cultural patterns (the Datoga), pointed to the potential role of androgen receptor gene polymorphism in male aggression and reproduction (number of offspring born) [ 148 , 149 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated that females prefer more masculine male partners, and males, in turn, more feminine looking females in such environment or in the absence of high-quality medical help [ 153 ]. It remains to be found out in the future, which sexually dimorphic traits may enhance individual survival probability to different degrees in males and females and show lesser variations between populations of modern humankind [ 34 ].…”
Section: Discussionmentioning
confidence: 99%